A novel magnetic resonance imaging‐based scoring system to predict outcome in neonates born preterm with intraventricular haemorrhage. (28th November 2021) - Goeral, Katharina; Kasprian, Gregor; Hüning, Britta M; Waldhoer, Thomas; Fuiko, Renate; Schmidbauer, Victor; Prayer, Daniela; Felderhoff‐Müser, Ursula; Berger, Angelika; Olischar, Monika; Klebermass‐Schrehof, Katrin
Abstract : Aim: To create a magnetic resonance imaging (MRI)‐based scoring system specific to neonates born preterm with intraventricular haemorrhage (IVH), which could serve as a reliable prognostic indicator for later development and might allow for improved outcome prediction, individually‐tailored parental counselling, and clinical decision‐making. Method: This retrospective, two‐center observational cohort study included 103 infants born preterm with IVH (61 males, 42 females; median gestational age 26wks 6d), born between 2000 and 2016. Term‐equivalent MRI was evaluated using a novel scoring system consisting of 11 items. A total MRI score was calculated and correlated with neurodevelopment between 2 years and 3 years of age. Prediction models for outcome were defined. Results: The proposed MRI scoring system showed high correlation and strong predictive ability with regard to later cognitive and motor outcome. The prediction models were translated into easy‐to‐use tables, allowing developmental risk assessment. Interpretation: The proposed MRI‐based scoring system was created especially for infants born preterm with IVH and enables a comprehensive assessment of important brain areas as well as potential additional abnormalities commonly associated with IVH. Thus, it better represents the severity of brain damage when compared with the conventional IVH classification. Our scoring system should provide clinicians with valuable information, to optimize parental counselling and clinical decision‐making.